Clinico-Epidemiological Study of Thalassemia in Wasit Governorate - Atta AH Mousa Al-Sarray (Journal of Global Pharma Technology, 2016)
Background: Globally, thalassemia is the most common genetic hemoglobin disorder. In the developing world, the majority of patients die before the age of 20 years. Objective: To determine the prevalence of thalassemia and different Clinico-epidemiological factors associated with thalassemic patients in Wassit governorate Subjects and Methods: A cross sectional study conducted at thalassemia center in Al-Kut hospital for Gynecology obstetrics and pediatric in Wasit governorate, included 425 patients, the data collection continued for the period of five months stating on 1st of March 2019 to 30th of July 2019. Results: The prevalence of thalassemia was 34.45% of the total patient attending Al-Kut Hospital for Gynecology Obstetrics and pediatrics during the period of the study with a mean ±SD age of patients 14.71±8.5years. Most cases from beta thalassemia, and major genotype regarding the genotype of thalassemia and clinical characteristics highly significant association were found between genotype and age of onset, age at first transfusion, frequency of blood transfusion, and regular blood transfusion. Regarding the complications of thalassemia higher percentage of study sample were iron overload, splenomegaly , protrusion of facial bones and teeth, (89.9%, 83.1%, 55.5%) respectively, while the lower percentage were visual impairments, hepatitis B, AIDS (5.6 %, 0.9%, 0.2%) respectively. Conclusion: The prevalence of thalassemia was 34.45% of the total patient attending Al-Kut Hospital for Gynecology Obstetrics and pediatrics during the period of the study Most cases from beta thalassemia, and major genotype significant association were found between genotype and age of onset, age at first transfusion, frequency of blood transfusion, and regular blood transfusion Recommendations: We recommend a comprehensive medical examination on the identification of pre-marital hemoglobin electrophoresis to enhance genetic counseling and to help reduce the transmission of these genetic diseases among generations, and use of the system-centered risk stratification model in order to individualize patient treatment for each.Keywords: Thalassemia, Hemoglobinopathies, Iraq, Prevalence, Wasit.